Association of Psoas Muscle Mass at Intensive Care Unit Admission With Physical Function and Post-discharge Destination in Survivors of Critical Illness - Kohei, Tanaka; Takamura, Daisuke; Nonaka, Shota; Yamada, Tomoki (Curēus (Palo Alto, CA), 2024)
Survivors of critical illness may have physical impairments, known as post-intensive care syndrome (PICS). Early screening for the risk of PICS is recommended to prevent PICS. Skeletal muscle mass is a clinically important indicator associated with various outcomes. This study aimed to examine the association of psoas muscle mass at intensive care unit (ICU) admission with the destination and physical function at hospital discharge. In this single-center retrospective cohort study, we reviewed the medical records of adult patients who had required emergency ICU admission and who had been intubated and mechanically ventilated. Psoas major muscle was measured as an indicator of skeletal muscle mass from abdominal computed tomography images at ICU admission. Physical function was assessed using the functional status score for the ICU and ICU mobility scale at hospital discharge. Multinomial logistic and multivariable linear regression were used to analyze the associations of the psoas muscle mass with the discharge destination and physical function at discharge. We enrolled 124 patients (79 men and 45 women) with a median (interquartile range) age of 72.0 (62.0-80.0) years; 39 (31.5%) were discharged to home, 50 (40.3%) were transferred to rehabilitation wards, and 35 (28.2%) were transferred to long-term care settings. The psoas muscle area and volume were 16.9 (11.3-20.6) cm and 228.3 (180.2-282.0) cm in home discharge patients, 17.5 (11.5-21.5) cm and 248.4 (162.0-311.4) cm in rehabilitation ward patients, and 15.9 (10.3-19.5) cm and 184.0 (137.0-251.1) cm in long-term care patients. The areas and volumes of the psoas muscle were not significantly different in the three groups. Furthermore, psoas muscle mass was not significantly associated with the discharge destination and physical function. Discharge destination and physical function at hospital discharge were not significantly associated with psoas muscle mass at ICU admission.